ON WEIGHTED CLASSES OF ENTIRE FUNCTIONS IN $\mathbb{C}^n$ - Petrosyan, A. I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
In the paper the weighted classes $A_{ω}^2(\mathbb{C}^n)$ t of entire functions of several complex variables are introduced. These classes depend on parameter-function $ω(x)$ and they are arbitrarily large. For functions belonging to $A_{ω}^2(\mathbb{C}^n)$ the integral representation is obtained.
Keywords: weighted classes; parameter-function; complex variables